СПОСІБ ВИМІРЮВАННЯ ЛОКАЛЬНИХ ЗМІН ЕЛЕКТРОПРОВІДНОСТІ РОЗЧИНІВ У ДИФЕРЕНЦІЙНИХ КОНДУКТОМЕТРИЧНИХ СИСТЕМАХ - Мельник, В.Г.; Борщов, П.І.; Дзядевич, С.В.; Саяпіна, О.Я. (Інститут електродинаміки Національної академії наук України, 2022)
A method for measuring local changes in the electrical conductivity of solutions using differential conductometric sensors is considered. The method makes it possible to significantly reduce the measurement error due to changes in the background electrical conductivity of the measuring medium when applying the test substance with non-identical parameters of equivalent electrical circuits of the sensor components. The bridge measuring circuit is brought to a quasi-balanced state, while the voltages in the sections of the working solution of the working and reference transducers of the sensor coincide in phase with each other, and their values are proportional to the conductivity of these sections. At the same time, changes in the background electrical conductivity of the solution do not lead to a change in the imbalance signal of the bridge circuit, which allows measuring the informative local change in the electrical conductivity of the working transducer with high sensitivity. The method can be used for highly sensitive and accurate quantification of solutions of electrically conductive substances in technological processes in the energy, chemical, and food industries, in the latest technologies, in particular in biosensor analyzers. The research results of the experimental sample of the conductometric analyzer are given. Ref. 9, table.